Astrophysics of "extreme" solar-like stars - Caballero-García, M. D.; Castro-Tirado, A. J.; Claret, A.; Gazeas, K.; Šimon, V.; Jelínek, M.; Cwiek, A.; Żarnecki, A. F.; Oates, S.; Jeong, S.; Hudec, R. (Revista Mexicana de Astronomia y Astrofisica Conference Series, 2016)
Only a few red dwarf flaring stars in the solar neighbourhood have undergone exceptional events called superflares. They have been detected with high-energy satellites (Swift) and have been proven to be powerful events (both in intensity and energy) and potentially hazardous for any extraterrestial life. The physics of these events can be understood as an extrapolation of the (much) weaker activity already occurring in the most powerful solar flares occurring in the Sun. Nevertheless, the origin (why?) of these superflares occur is currently unknown. A recent study presents the optical and X-ray long-term evolution of the emission by the super-flare from the red-dwarf star DG CVn undertaken in 2 014. In that paper we comment on the context of these observations and on the properties that can be derived through the analysis of them.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; gamma-rays: observations; stars: activity; stars: flares